Echoes of the Absent: Hauntology, Narratology, and the Spectral Art of Translation - Pecastaing, Sandy (Labyrinth, 2025)
The aim of this article is to examine the relevance of Jacques Derrida's concept of hauntology to literary criticism and translation studies, with a focus on Edgar Allan Poe's The Raven and its French translations. It demonstrates how hauntology—emphasizing the spectral interplay between presence and absence, origin and trace, and meaning and deferral—reframes texts as sites of revenance: haunted spaces of fragmented meanings and deferred interpretations. By analyzing the challenges of translating The Raven's rhythmic complexity, phonetic resonance, and iconic refrain, "nevermore," this study highlights the text's spectral nature and resistance to closure. Additionally, the paper seeks to provide a new perspective on the dispersion of meaning in translation. It shows how French translations by Baudelaire, Mallarmé, and others exemplify Derrida's notion of dissemination, contributing to contemporary discussions in literary studies, translation theory, and philosophical criticism.